Increasing Mall Patronage Intention: A Case Study of College Students - Serevina, Vira; Hartono, Natalia; Laurence, Laurence (RSF Conference Series: Business, Management and Social Sciences, 2022)
An initial discussion with the mall's management reveals that one of the issues is determining how to increase customer mall patronage intention. College students were the mall's primary visitors due to its proximity to the university. This study aimed to increase the customer's mall patronage intention (i.e., the desire to become a loyal customer) toward the mall. The relationships and effects of its variables are examined in light of their mall experience. The model is built based on previous research, and the variables within the model are explored using Partial Least Square Structural Equation Modelling (PLS-SEM) to ensure that the model fits the Indonesian context. The questionnaire was distributed to the university's students and recorded using Google Forms. The response rate was 50%, with 54 usable responses. The validity and reliability tests were conducted, followed by measurement model assessment, structural model assessment, and statistical significance. The model's findings indicate that the mall's entertainment, satisfaction, and aesthetic experience all have a significant effect on mall patronage intention. In addition, students' purchase behaviour is positively influenced by emotional and perceived value.